Effect of Polishing Technique on Flexural Strength of Glass-Ceramics. (2022) - Maier, E.; Gebler, P.; Lammers, P.; Belli, R.; Lohbauer, U.; Pelka, M.
Abstract : Purpose/Aim: Aim of the study was to evaluate the influence of polishing on the flexural strength of dental glass-ceramic materials performed according to chairside techniques, laboratorial procedures or glazed. Materials and Methods: Specimens were produced of two dental ceramics (IPS e.max CAD/IPS e.max Press, both Ivoclar Vivadent, Schaan, Liechtenstein) as bars of 4 ×3 x 25 mm. Specimens were grinded wet with a rough diamond-copper wheel (D19) to standardize a rough surface (served as negative control, group 5). To simulate chairside conditions students of the 10th semester polished one side of the bars with either Diapro (two-step system, group 1) or Diapol (three-step system, group 2) (both from EVE Ernst Vetter GmbH, Keltern, Germany) dry with a KAVO handpiece. The positive control (group 3) was polished in laboratory with an automatic polishing machine (Buehler) with SiC papers up to 4000 grit under water-cooling. Group 4 was glazed (Crystal/Glaze Spray, Ivoclar) following manufacturers intructions. Afterwards all specimens were tested for flexural strength in a four-point-bending test. Stress at fracture was analyzed using Weibull statistics. Results: The unpolished negative control group 5 showed the lowest mean flexural strength values for both materials. The chairside polishing groups (1/2) showed the highest mean flexural strength values. For e.max CAD those were significantly higher than in group 3 (lab polish), for e.max Press no significant difference between those groups could be found. Group 4 (glaze) reached similar mean flexural strength values to lab polishing (3) for e.max CAD; for e.max Press the values were significantly lower than in all polished groups (1-3). Conclusions: Polishing of dental ceramics increases flexural strength, independent if done dry chairside or in laboratory under water-cooling. Glazing can increase strength depending on material but is not more effective than polishing.